Evaluation Of Pegasus Airlines' Sustainability Performance Using SBSC-Based Critic And Copras Methods (Third Sector Social Economic Review, 2025)
In the face of growing environmental concerns, economic volatility, and evolving societal expectations, sustainability has become a strategic imperative for organizations. The aviation industry, due to its high operational emissions and energy consumption, is under increasing pressure to align growth targets with environmental and social responsibility. This study evaluates the sustainability performance of Pegasus Airlines from 2021 to 2024 through the Sustainability Balanced Scorecard (SBSC) framework, which integrates financial, customer, internal process, learning and growth, and socio-environmental dimensions. The CRITIC method was employed to objectively determine the weights of 18 performance indicators, accounting for their contrast intensity and interdependencies. Subsequently, the COPRAS method was used to rank annual performance across the evaluated years. Findings indicate that 2021 was the most successful year in terms of sustainability performance, while 2023 ranked the lowest. This integrated approach contributes to the development of a more dynamic and objective sustainability assessment model for airline companies, supporting both retrospective analysis and strategic foresight.
Keywords: türkçe; Sustainability; Airline Management; SustainibilityBalanced Scorecard; CRITIC; COPRAS